Acoustic Panels from Waste Eelgrass: Benefits and Challenges of a Circular Business Model - Kjærsgaard, Niels C.; Salvador, Rodrigo; Eriksen, M. Lynn; Eriksen, M. Lynn; Hedegaard, Michael; Lund, Victor; Knudby, Torben (European Journal of Sustainable Development, 2025)
This paper explores the transformation of waste eelgrass (Zostera marina), commonly found along European coastlines, into sustainable acoustic panels through circular business models (CBMs). The study adopts a qualitative, exploratory approach involving literature review, participatory stakeholder workshops to identify and assess the challenges and opportunities in this innovation ecosystem. Key insights are derived from the Power Bio project, which facilitated co-creation of business model prototypes with municipalities, producers, and biomass collectors. The research highlights significant environmental benefits such as carbon reduction and beach aesthetics improvement, alongside economic advantages including premium pricing and cost avoidance. However, it also uncovers barriers like supply chain instability, regulatory fragmentation, and low public awareness. Methodologically, the study draws on tools like the Triple Layered Business Model Canvas (TLBMC) and design thinking to integrate sustainability and stakeholder engagement. By aligning theoretical insights with empirical stakeholder input, the paper offers a grounded model for municipalities and entrepreneurs aiming to repurpose coastal biomass waste. It contributes both to the academic discourse on circular bioeconomy and provides actionable recommendations for sustainable building practices. The findings align with EU goals on climate neutrality and sustainable construction, offering a scalable pathway from coastal nuisance to green innovation. Keywords: Circular Economy; Bioeconomy; Biomass Waste; Circular Business Model; Acoustic Panels; Build Environment